Production of active coal from pyrolyzed wood wastes by alkaline activation of KOH - Kuzmin, Oleg; Tamarkina, Julia; Shendrik, Tatiana; Zubkova, Valentyna; Koval, Olha; Roman, Tatiana (My University, 2017)
The purpose of this publication is to search for alternative materials – food industry wastes; valuation of it’s use in the production of sorbents. Метою публікації є пошук альтернативних матеріалів – відходів харчової промисловості; оцінка перспективності їх використання при виробництві сорбентів.
Keywords: піроліз; відходи; активація; нанопори; pyrolysis; wastes; activation; nanopores; adsorbent; кафедра технології ресторанної і аюрведичної продукції